Information Systems: Intelligent Information Processing Systems, Natural Language Processing, Affective Computing and Artificial Intelligence, and an Attempt to Build a Conversational Nursing Robot (IntechOpen, 2021)
This book deals with intelligent information processing systems related to natural language processing, text mining, web information processing, and nursing and caring robot technologies. It introduces the latest trends and past research results of researchers in a wide range of fields related to knowledge information processing, which is one of the ultimate goals of information processing technology and is necessary for making artificial brains useful in our society.